An Analysis of The Effect of Social Media Marketing Through Instagram Reels on Impulse Buying of Erigo Products Among College Students - Irfani Margi Prakoso; Ratu Permata Salim; Rian Nur Firmansyah; Erwinsyah Erwinsyah (Journal of Management, Entrepreneurship, and Tourism, 2026)
This study investigates the effect of social media marketing through Instagram Reels on the impulse buying behavior of Erigo products among college students in Jakarta. The research adopts a quantitative cross sectional survey design involving undergraduate students who actively use Instagram and have been exposed to Instagram Reels content related to fashion products. Data were collected through a structured online questionnaire and analyzed using descriptive statistics and simple linear regression. The findings indicate that Instagram Reels marketing exerts a positive and significant influence on impulse buying behavior. Visual attractiveness, content creativity, audio appeal, information quality, and engagement capability were perceived positively by respondents and contributed to stronger purchasing impulses. The results further reveal that emotional stimulation, social interaction, trend following tendencies, and Fear of Missing Out intensify spontaneous purchase intentions among students. Visual attractiveness emerged as the most influential marketing dimension, while emotional urge represented the strongest indicator of impulse buying. The study contributes to consumer behavior and digital marketing literature by explaining how short video content shapes purchasing decisions through psychological and emotional mechanisms. Practical implications highlight the importance of developing engaging and emotionally appealing Instagram Reels strategies to enhance marketing effectiveness within the fashion industry.